Ultraviolet light‐irradiated photocrosslinkable chitosan hydrogel to prevent bone formation in both rat skull and fibula bone defects. (9th March 2012) - Tsuda, Yoshifumi; Hattori, Hidemi; Tanaka, Yoshihiro; Ishihara, Masayuki; Kishimoto, Satoko; Amako, Masatoshi; Arino, Hiroshi; Nemoto, Koichi
Abstract In the field of orthopaedic surgery, an orthopaedic surgeon sometimes requires to suppress excessive bone formation, such as ectopic bone formation, ossifying myositis and radio‐ulnar synostosis, etc. Ultraviolet (UV) light irradiation of a photocrosslinkable chitosan (Az–CH–LA) generates an insoluble hydrogel within 30 s. The purpose of this study was to evaluate the ability of the photocrosslinked chitosan hydrogel (PCH) to inhibit bone formation in an experimental model of bone defect. Rat calvarium and fibula were surgically injured and PCH was implanted into the resultant bone defects. The PCH implants significantly prevented bone formation in the bone defects during the 4 and 8 week observation periods. In the PCH‐treated defects, fibrous tissues infiltrated by inflammatory cells were formed by day 7, completely filling the bone defects. In addition to these findings, expression of osteocalcin and runt‐related gene 2 (RUNX2) mRNA, both markers of bone formation, was lower in the PCH‐treated defects than in the controls. In contrast, collagen type 1α2 and α‐smooth muscle actin (α‐SMA) mRNA levels were significantly higher in the PCH‐treated defects after 1 week. PCH stimulated the formation of fibrous tissue in bone defects while inhibiting bone formation. Thus, PCH might be a promising new therapeutic biomaterial for the prevention of bone formation in orthopaedic surgery. Copyright © 2012 John Wiley & Sons, Ltd.